Sex differences in ventricular arrhythmia, atrial fibrillation and atrioventricular block complicating acute myocardial infarction - Hilmi Alnsasra; Hilmi Alnsasra; Gal Tsaban; Gal Tsaban; Jean Marc Weinstein; Jean Marc Weinstein; Mhamad Nasasra; Mhamad Nasasra; Tal Ovdat; Roy Beigel; Katia Orvin; Moti Haim; et al. (Frontiers in Cardiovascular Medicine, 2023)
BackgroundAcute myocardial infarction (AMI) complicated by tachyarrhythmias or high-grade atrioventricular block (HAVB) may lead to increased mortality.PurposeTo evaluate the sex differences in patients with AMI complicated by tachyarrhythmias and HAVB and their associated outcomes.Materials and methodsWe analyzed the incidence rates of arrhythmias following AMI from the Acute Coronary Syndrome Israeli Survey database from 2000 to 2018. We assessed the differences in arrhythmias incidence and the associated mortality risk between men and women.ResultsThis cohort of 14,280 consecutive patients included 3,159 (22.1%) women and 11,121 (77.9%) men. Women were less likely to experience early ventricular tachyarrhythmia (VTA), (1.6% vs. 2.3%, p = 0.034), but had similar rates of late VTA (2.3% vs. 2.2%, p = 0.62). Women were more likely to experience atrial fibrillation (AF) (8.6% vs. 5.0%, p < 0.001) and HAVB (3.7% vs. 2.3%, p < 0.001). The risk of early VTAs was similar in men and women [adjusted Odds Ratio (aOR) = 0.76, p = 0.09], but women had a higher risk of AF (aOR = 1.27, p = 0.004) and HAVB (aOR = 1.30, p = 0.03). Early [adjusted hazard ratio (aHR) = 2.84, p < 0.001] and late VTA (aHR =- 4.59, p < 0.001), AF (aHR = 1.52, p < 0.001) and HAVB (aHR = 2.83, p < 0.001) were associated with increased 30-day mortality. Only late VTA (aHR = 2.14, p < 0.001) and AF (aHR = 1.44, p = 0.002) remained significant in the post 30 days period.ConclusionsDuring AMI women experienced more AF and HAVB but fewer early VTAs than men. Early and late VTAs, AF, and HAVB were associated with increased 30-day mortality. Only late VTA and AF were associated with increased post-30-day mortality.